Global analysis of transcript and protein levels across the Plasmodium falciparum life cycle - Le Roch, Karine G.; Johnson, Jeffrey R.; Florens, Laurence; Zhou, Yingyao; Santrosyan, Andrey; Grainger, Munira; Yan, S. Frank; Williamson, Kim C.; Holder, Anthony A.; Carucci, Daniel J.; Yates, John R.; Winzeler, Elizabeth A.

(untitled) (Genome Research, 2004)
To investigate the role of post-transcriptional controls in the regulation of protein expression for the malaria parasite, Plasmodium falciparum, we have compared mRNA transcript and protein abundance levels for seven different stages of the parasite life cycle. A moderately high positive relationship between mRNA and protein abundance was observed for these stages; the most common discrepancy was a delay between mRNA and protein accumulation. Potentially post-transcriptionally regulated genes are identified, and families of functionally related genes were observed to share similar patterns of mRNA and protein accumulation.